Quest For Beauty And Novelty Of Women - Anand Kumar Minj (International Journal of Psychosocial Rehabilitation, 2020)
This research paper examines the varied philosophical notions of beauty and novelty. It explores the traditional perspective, which highlights the organisation of essential components into a consistent entirety and the significance of balance, concord, and balance. The utopian viewpoint, influenced by thinkers such as Plato, Schiller, and Hegel, considers aesthetics as flawless harmony and a connection between the tangible and ethereal domains. The pleasure-seeker approach links attractiveness with enjoyment and the personal encounter of joy. Furthermore, the synopsis explores the correlation between aesthetics and beauty or yearning, a motif present in diverse philosophical lineages. In general, this expedition provides perspectives into diverse philosophical comprehendings of attractiveness and innovation, illuminating its manifold essence.